Eccentric compression performance of jointed precast concrete-encased concrete-filled steel tube columns with dry connections - Zhu, Gaoming (2024)
Concrete-encased concrete-filled steel tube (CECFST) columns have recently been regarded as the optimum option for high-rise or heavy-loaded buildings due to superior structural resistance over traditional concrete-filled steel tube (CFST) and reinforced concrete (RC). Thus, in developed countries with severe manpower shortages such as Singapore, advanced precast dry connections were proposed for the CECFST columns to facilitate construction and tackle manpower crunch. Moreover, current research shows that the proposed connection has comparable structural resistance with conventional cast-in-place (CIP) connections, demonstrating huge application potential. However, the existing research is only limited to the performance of precast connections without any experimental studies on jointed columns, which hinders the implementation of the precast connections in engineering of practices. In this paper, to address this research gap, a comprehensive experimental programme was initiated, followed by extensive numerical studies. A total of six intermediate and slender jointed precast columns were tested to investigate the effect of precast connections on load-carrying behaviour of the jointed CECFST columns by considering column slenderness, connection detailing, connection position and load eccentricity. Besides experimental studies, extensive 3D finite element (FE) simulations were performed to investigate the relationship between connection integrity, constructability, and load-carrying performance of the jointed CECFST columns. The numerical studies showed that implementing the conventional “Equivalent to CIP” concept into the design of jointed precast CECFST columns would significantly compromise the constructability of such columns. To address this concern, a performance-based design method was proposed for jointed CECFST columns. Parametric studies showed that adopting the performance-based design method could not only improve constructability but also achieve sufficient column resistance.